Bahşayiş Lügati'nde Görülen Tercüme Teknikleri ve Filolojik Problemler - Turan, Fikret (İlim Yayma Cemiyeti, 2001)
Bahşayiş Lügati is one of the earliest lexicons on Early Oghuz Turkish composed as an interlinear translation of an Arabic-Persian dictionary. It includes many archaic lexical and syntactical forms and features. This article is concerned with the analysis of methods and structures of word, word groups and sentences appear as the Turkish translation of Arabic and Persian vocabulary as well as of philological problems remaining.
Translation Techniques and Philological Problems in Bahşayiş Lügati
Keywords: Bahşayiş Lügati; Old Oghuz Turkish; Turkish Lexicography; Translation Methods